Searching Meaning of Jihad for Indonesian Muslim in the Post Reformed Era of Indonesian Polity - Hammam Hammam; Rizwanur Rahman (IAIN Pekalongan, 2020)
This paper aims to analyse the progressive meaning of jihad not only as religious discourses but also teaching practised by Indonesian Muslim from long time ago until the reformed era. In this political transition to democracy, Indonesian government has encountered many ideologies including transnational Islamic movements that promote another idea of jihad containing a lot of tension, hatred, and violence such as war, exclusive, intolerance, monolithic point of view, and single truth claim. These ideas have been extremely different from Indonesian Muslim scholars and cleric thought that have interpreted jihad locally and has been practised harmoniously for long time. Therefore to identify the concept of jihad in democratic era will be a solution of contemporary development of Indonesian Islam as well as promoting harmonious coexistence. Method used in this research is narrative analysis, written and spoken texts are categorised as data. The data are focused on the concept of jihad which is classified into moderate jihad and immoderate jihad as constructed by Indonesian Muslim scholars especially those who are affiliated with Muhammadiyah and Nahdltul Ulama. Finding of this research is that jihad for Indonesian Muslim in the post reformed era of Indonesian polity is defined as any struggle or effort made with the right faith and with the right intention in order to strengthen the word of truth, to bring about peace, to help humanity without the involvement or greed of personal gain, fame, and other fortunes that continue until the end of the day